2019
DOI: 10.31211/interacoes.n37.2019.a8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Nexus Between Family Size Planning and Retirement Planning in Ghana

Abstract: The study articulates the perspectives and attitudes of workers in an attempt to uncover thoughts and ideas in relation to the phenomena of family size planning and retirement planning. Use was made of both quantitative and qualitative datasets. The sample [n=442] was selected using a multi-stage sampling technique. The paper finds that there is a link between family planning and retirement planning. The reasons for this nexus encompass the fact that large family sizes may inhibit saving abilities. Further, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Forty-three of the works reviewed were empirical and involved collection of primary data. Apart from articles by Dovie (2018aDovie ( , 2018bDovie ( , 2019Dovie ( , 2020 and also Oteng et al (2018), which employed a mixed methods methodological approach, all the empirical works reviewed were purely quantitative, and employed questionnaires in data collection. In terms of temporal design, the researchers found that all the empirical works were cross-sectional.…”
Section: Design and Methodological Approachmentioning
confidence: 99%
“…Forty-three of the works reviewed were empirical and involved collection of primary data. Apart from articles by Dovie (2018aDovie ( , 2018bDovie ( , 2019Dovie ( , 2020 and also Oteng et al (2018), which employed a mixed methods methodological approach, all the empirical works reviewed were purely quantitative, and employed questionnaires in data collection. In terms of temporal design, the researchers found that all the empirical works were cross-sectional.…”
Section: Design and Methodological Approachmentioning
confidence: 99%
“…In other words, it is pertinent for both men and women. The process of retirement planning comprises several pillars, namely the identification and articulation of retirement aspirations, pre-retirement education (PRE), and a host of others (Dovie, 2019d). However, there are differences in planning towards retirement in terms of the sector of the economy in question, albeit formal or informal.…”
Section: Gender and Retirementmentioning
confidence: 99%